2013
DOI: 10.1371/journal.pone.0075018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Relationship between N-Terminal Acetylation of α-Synuclein and Fibril Formation Rates by NMR and Fluorescence

Abstract: Aggregation of α-synuclein (αSyn), the primary protein component in Lewy body inclusions of patients with Parkinson’s disease, arises when the normally soluble intrinsically disordered protein converts to amyloid fibrils. In this work, we provide a mechanistic view of the role of N-terminal acetylation on fibrillation by first establishing a quantitative relationship between monomer secondary structural propensity and fibril assembly kinetics, and secondly by demonstrating in the N-terminal acetylated form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 51 publications
(61 reference statements)
4
43
0
Order By: Relevance
“…The most striking result from comparing the aggregation behavior of low pH ABB (not amyloid-forming) and BBX (fibrilforming) chimeric proteins was that the N-terminal and ␤-NAC domains together play a key role in the ability to form fibrils at mildly acidic pH. Although the NAC domain is necessary for fibrillation, in ␤S the N-and C-terminal domains regulate the NAC domain-mediated fibrillation inducing interactions, with interactions between the N-terminal and NAC domains playing a more crucial role in the stabilization of the ␤S fibril architecture similar to previous observations in ␣S (67)(68)(69). The C-terminal domain, which is highly enriched in negative charges, and is thus expected to be more pH-sensitive, does not appear to provide the required pH-sensitive stabilizing interactions, but may instead contribute to pH-dependent aggregation via C-terminal inhibitory (N-C and NAC-C) intra/inter-chain interactions as evidenced by the differing lag times (but highly similar fibril topology) between all C-terminally swapped chimeras (supplemental Figs.…”
Section: Discussionsupporting
confidence: 76%
“…The most striking result from comparing the aggregation behavior of low pH ABB (not amyloid-forming) and BBX (fibrilforming) chimeric proteins was that the N-terminal and ␤-NAC domains together play a key role in the ability to form fibrils at mildly acidic pH. Although the NAC domain is necessary for fibrillation, in ␤S the N-and C-terminal domains regulate the NAC domain-mediated fibrillation inducing interactions, with interactions between the N-terminal and NAC domains playing a more crucial role in the stabilization of the ␤S fibril architecture similar to previous observations in ␣S (67)(68)(69). The C-terminal domain, which is highly enriched in negative charges, and is thus expected to be more pH-sensitive, does not appear to provide the required pH-sensitive stabilizing interactions, but may instead contribute to pH-dependent aggregation via C-terminal inhibitory (N-C and NAC-C) intra/inter-chain interactions as evidenced by the differing lag times (but highly similar fibril topology) between all C-terminally swapped chimeras (supplemental Figs.…”
Section: Discussionsupporting
confidence: 76%
“…In line with that, many studies have shown that NTA can stabilize an N-terminal α-helix (Shoemaker et al, 1987; Fairman et al, 1989; Chakrabartty et al, 1993; Doig et al, 1994; Greenfield et al, 1994; Jarvis et al, 1995; Fauvet et al, 2012; Kang et al, 2012, 2013). …”
Section: Introductionmentioning
confidence: 60%
“…Indeed, NatB has been identified in a genetic screen for deletion mutants with mislocalization of α-synuclein, and the knockout of NatB diminishes the membrane localization of α-synuclein in yeast (Zabrocki et al, 2008). Furthermore, NTA of α-synuclein has been shown to promote its soluble, intrinsically alpha-helical structure, thereby inhibiting aggregation (Kang et al, 2012, 2013), promoting membrane/vesicle binding (Maltsev et al, 2012; Bartels et al, 2014) and interaction with calmodulin (Gruschus et al, 2013). Another group showed that NTA has no major influence on α-synuclein aggregation, synaptosomal membrane binding and only slightly increased helicity of the N-terminal region as shown by NMR, static light scattering, and sedimentation assays on recombinantly expressed α-synuclein (Fauvet et al, 2012).…”
Section: Mammalsmentioning
confidence: 99%
“…The ‘red shifted’ (from 450 to 482 nm) and enhanced fluorescence of ThT when it binds to amyloid forms of α-syn has been used for fluorescence assays of the effects of mutations on both the extent of aggregation 26,46,68 and as a probe of amyloid formation kinetics 26,41,68,69 and amyloidogenesis inhibition 13 . While the increase in fluorescence intensity observed for other amyloid systems is much greater 43,48 , the increase for α-syn is still readily detected.…”
Section: Methodsmentioning
confidence: 99%
“…This reflects enhanced helicity that is limited to residues 1–9. Evidence presented to date 41 indicates that enhanced helicity in the residue 14 – 31 and 50 – 57 spans enhances fibrilization but that the inhibitory effect of N-terminal helicity is more dramatic. Thus non-acetylated α-syn remains a suitable model for biologically relevant aggregation studies.…”
mentioning
confidence: 99%